2015
DOI: 10.1159/000439540
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities and Patterns of Cervical Spine Injuries in Children and Adolescents: A Retrospective Series of 84 Patients from a Single Institute

Abstract: Cervical spine injuries occur infrequently in children but are associated with significant disability and mortality. A retrospective analysis was performed of 84 consecutive pediatric spine injuries treated at our institute from January 2002 to December 2011. The mean age was 14.7 years. There were 18 patients (21%) in group A (0-12 years) and 66 patients (79%) in group B (13-18 years). Overall, injury was more common in boys (ratio of 6:1). Trivial fall was the predominant cause in group A and fall from heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Good postoperative follow-up has been associated with favorable outcomes after cervical trauma repair. 1 After successfully repairing the fracture and dislocation, our patient is walking and using his hands in part due to consistent physical and occupational therapy. He is speaking well and participating in school, despite his early oral aversion, due to regular speech therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Good postoperative follow-up has been associated with favorable outcomes after cervical trauma repair. 1 After successfully repairing the fracture and dislocation, our patient is walking and using his hands in part due to consistent physical and occupational therapy. He is speaking well and participating in school, despite his early oral aversion, due to regular speech therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Although few cases of favorable outcomes of cervical dislocation after birth have been reported in the past, 10,11,24 the incidence of such an injury is deemed to be higher than reported. 1 In infants, the fulcrum of cervical spine movement is located at C1-3, leading to a majority of injuries in this region. Such injuries occur due to hyperflexion or hyperextension mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These differences cause unique patterns of injuries, and generally prognosis is better. 22 Children under 2 years of age rarely sustain bony cervical spine injury but are prone to cervical cord injury due to relative hypermobility of spine. Autopsies have shown that bony spinal column can withstand 2 inches of stretching, whereas neurovascular structures shear at a quarter of an inch stretch.…”
Section: Care Of Cervical Spinementioning
confidence: 99%
“…The classification of odontoid fractures given by Anderson and D'Alonzo is the most accepted 6 . Non‐operative treatments, such as traction, reduction, and external orthosis, are common management options for type I odontoid fractures and achieve a high fusion rate 7–10 . However, for unstable and displaced fractures, such as type II and rostral type III fractures, surgical intervention is required to increase the fusion rate and avoid serious consequences, such as medullary compression and dynamic instability 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 Non‐operative treatments, such as traction, reduction, and external orthosis, are common management options for type I odontoid fractures and achieve a high fusion rate. 7 , 8 , 9 , 10 However, for unstable and displaced fractures, such as type II and rostral type III fractures, surgical intervention is required to increase the fusion rate and avoid serious consequences, such as medullary compression and dynamic instability. 11 , 12 Compared to traditional surgeries, anterior screw fixation can preserve the normal range of atlantoaxial motion and has excellent fusion rates.…”
Section: Introductionmentioning
confidence: 99%